Palladium encapsulated nanofibres for scavenging ethylene from sapota fruits - Gundewadi, Gajanan; Rudra, Shalini Gaur; Prasanna, Radha; Banerjee, Tirthankar; Singh, Sanjay Kumar; Dhakate, Sanjay R.; Gupta, Ashish; Anand, Anjali (Frontiers in Nutrition, 2022)
Scavenging ethylene is a useful intervention during transportation and storage of tropical climacteric fruits like sapota. Sapota (Manilkara achras Mill.) is a delicious tropical fruit with very high respiration rate and poor shelf life. To prolong its post-harvest shelf life, the use of palladium chloride in electrospun nanomats was evaluated at concentration varying from 1-4% levels. Encapsulation of 1-2% PdCl2 in nanomats increased the ethylene scavenging capacity (ESC) by 47-68%. Although, upon encapsulation, both PdCl2 and potassium permanganate showed significantly same ethylene scavenging activity, the efficacy of PdCl2 was found better in presence of sapota fruits. The PdCl2 nanomats were brighter (L*> 73) in colour compared to potassium permanganate mat. Placement of nanomats (2×9 cm2) in corrugated fibre board boxes in which the sapota were packed showed higher quality indices (firmness, TSS, ascorbic acid, phenolics along with lower PLW and respiration rate during the 8 days storage period. Compared to control (8.35%), physiological loss in weight of 4.47% was recorded in fruits stored with ethylene scavenging nanomats. PdCl2 encapsulated PVA nanomats can emerge as a promising option for retention of quality in fruits during storage and transit.